Terapi Pijat Punggung dengan Alat Pijat Kayu Kaki Tiga Menurunkan Tekanan Darah pada Lansia dengan Hipertensi - Ayu Putri Laksmidewi, Ni Kade Mas; Mertha, I Made; Gede Ngurah, I Gusti Ketut (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2024)
Hypertension in the elderly is a degenerative disease caused by increased arterial pressure in accordance with age, aortic regurgitation, and the degenerative process that occurs in the body where persistent blood pressure increases with systolic blood pressure above 140 mmHg and diastolic blood pressure above 90 mmHg. Efforts that can be made as an alternative to non-pharmacological therapy, one of which is the provision of back massage therapy with a three-legged wooden massage tool. The purpose of this study was to determine the effect of giving back massage therapy with a three-legged wooden massage tool on blood pressure in the elderly with grade one hypertension. This type of research is pre-experimental with the design used one group pretest-posttest design using sampling techniques, namely non probability with purposive sampling. The number of samples used in this study were 16 elderly respondents with hypertension. The research was conducted in April 2023. The results showed that the average systole and diastol blood pressure before treatment was 158,94/92,81 mmHg with the average MAP calculation before treatment was 114,85 mmHg. The average systole and diastol blood pressure after treatment was 140,19/83,06 mmHg with an average MAP calculation after treatment of 102,10 mmHg. The results of statistical tests using paired t-test obtained a p value of 0,000 which stated that there was a significant difference in blood pressure before and after treatment. Based on this, it is recommended to the health service unit to make back massage therapy with a three-legged wooden massage tool as a non-pharmacological therapy in treating hypertensive patients, especially in the elderly group.